International Certification and Accreditation of The Vocational Education in The Business/Industry Field - *, Roemintoyo (Proceeding of International Conference on Teacher Training and Education, 2016)
Quality control of ins titutions of higher education teacher training/LPTK, it seems that needs to be a renewal in order to adjustment with the demands of the user. The one that should be re-examined, associated with the conceptual foundation and the existence of independent institutional. Therefore, in this paper, developed a conceptual activities concerning the accreditation of vocational education institution as well as its implications.